Securing Financial Stability: Problems and Prospects for New EU Members - Michael C Bonello; Fabrizio Saccomanni; Claudia M. Buch; Jörn Kleinert; Peter Zajc (SUERF - The European Money and Finance Forum, 2003)
1) Stability Oriented Monetary and Prudential Policies in EU Accession Countries, by Michael C. Bonello 2) Ensuring Financial Stability: Global and European Perspectives, by Fabrizio Saccomanni 3) Foreign Bank Ownership: A Bonus or Threat for Financial Stability? by Claudia M. Buch, Jörn Kleinert and Peter Zajc
Keywords: E52; E58; F33; F36; G15; G21; G28; 330; Price stability; EU financial market integration; macroeconomic policy; monetary policy; EMU; capital flows and banking efficiency; financial integration and stability; transition economies; foreign direct investment; liquidity shocks; Finanzmarkt; Finanzsektor; EU-Mitgliedschaft; Osteuropa